How perceptions of physique can influence customer satisfaction in health and fitness centres - Smith, James; Murray, D.; Howat, G. (Routledge, 2014)
Numerous studies have established the link between service quality, satisfaction and loyalty in recreation and fitness settings. However, few studies in the recreation and fitness area have considered the role that one's appearance may play in influencing this relationship. This study of 294 customers of mixed-sex group fitness classes employed structural equation modelling to find general support for the following service quality model adapted from health-care services and health and fitness centres: process service quality → outcome service quality → satisfaction → loyalty. However, of particular interest was that the level of comfort a customer has in their physique significantly and negatively impacted the relationship between staff-oriented service quality and the attainment of outcomes such as improved health, mood, energy and fitness.